2019
DOI: 10.1111/eci.13064
|View full text |Cite
|
Sign up to set email alerts
|

Plasma sMer, sAxl and GAS6 levels correlate with disease activity and severity in lupus nephritis

Abstract: Objective The purpose of this study is to determine whether TAM receptors and ligands associated with the activity and severity of lupus nephritis. Methods Clinical data were statistically analysed and studied in 122 SLE patients, diagnosed from 2013 to 2016 in First Hospital Affiliated to Harbin Medical University. Levels of TAM receptors and ligands in the plasma of 122 SLE patients were measured by ELISA. Renal biopsies were performed to confirm lupus nephritis (LN) by histopathology in 68 patients. The ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 43 publications
(108 reference statements)
1
17
0
Order By: Relevance
“…Significantly elevated concentrations of plasma sAxl in SLE patients were repeatedly reported by different groups to correlate with disease activity and severity in lupus [48, 52, 54, 55] and lupus nephritis [52]. Plasma levels of sAxl followed the same trend as the plasma levels of sMer.…”
Section: Tam Ligands and Soluble Tam In Sle Pathogenesismentioning
confidence: 57%
See 2 more Smart Citations
“…Significantly elevated concentrations of plasma sAxl in SLE patients were repeatedly reported by different groups to correlate with disease activity and severity in lupus [48, 52, 54, 55] and lupus nephritis [52]. Plasma levels of sAxl followed the same trend as the plasma levels of sMer.…”
Section: Tam Ligands and Soluble Tam In Sle Pathogenesismentioning
confidence: 57%
“…Several groups made further association analysis of sMer levels with clinical and serological parameters. A strong association of higher plasma levels of sMer with nephritis was reported by three groups [49, 52, 53]. Zhu et al studied 108 Chinese SLE patients and found that plasma levels of sMer were significantly elevated in patients with proteinuria compared to those without increased urinary protein [53].…”
Section: Tam Ligands and Soluble Tam In Sle Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…On these bases, Gas6 and its soluble receptors have been proposed as biomarkers in different human conditions [21,22], specifically in autoimmune diseases [23][24][25][26]. In the present study, we aim to evaluate Gas6 and sAxl and sMer as potential biomarkers for cardiopulmonary complications of SS and SSD.…”
Section: Introductionmentioning
confidence: 99%
“…The extracellular domain of AXL is reported to be shed from the cell surface by proteases and deposited in blood [13,14]. Serum concentrations of this soluble AXL and the Gas6 ligand increase in patients with class 3 or 4 lupus nephritis and are well correlated with the disease activity index [15][16][17][18][19]. Moreover, soluble AXL decreases in patients responding to conventional therapy, but remains stable in non-responders [20].…”
Section: Introductionmentioning
confidence: 99%